Performance of no-till corn precision planter equipped with row cleaners - Li, Yang; Rui, Zhang; Nana, Gao; Tao, Cui; Quanwei, Liu; Dongxing, Zhang (International Journal of Agricultural and Biological Engineering, 2015)
In the continuous annual wheat-corn cropping area of North China Plain, no-till planting that promotes soil conservation and crop yield while reducing operation cost has been gradually accepted by local farmers. However, previous wheat residue is the main limiting factor affecting the performance of existing planters in placing seeds at uniform spacing and optimum depth in residue covered fields. In order to solve this problem, a kind of ground-wheel-driven row cleaner was designed, developed and mounted on row units of a four-row pneumatic precision planter. The planter has two adjacent row units equipped with the newly designed row cleaners and the other two adjacent row units equipped with the commonly used inactive row cleaners. This was used for planting at three forward speeds (4 km/h, 6 km/h and 8 km/h) into half residue (HR) and whole residue (WR) plots. The amount of residue removal, seeding depth, emergence rate and indices of uniformity in seed spacing (missing-seeding index, quality of feeding index and precision index) were measured. The newly designed row cleaner performed better with regard to residue removal, with the average percentage of residue cleared as 63.0% compared to 40.3% for the inactive row cleaner. For the HR and WR plots, percentage of residue cleared of the newly designed row cleaner reached 57.1% and 68.9% respectively, suggesting that the newly designed row cleaner can work more effectively at high residue level. By contrast, with the percentage of residue cleared of the inactive row cleaner as 43.1% and 37.5% in HR and WR plots, suggesting that the inactive row cleaner just can work effectively under low residue condition. Values of missing-seeding index, QFI, precision index, coefficient of variation of depth and percent emergence for the newly designed row cleaner under whole residue level are comparable to those for the inactive row cleaner under half residue level. The result indicates that the effect of using the newly designed row cleaner is equal to that of reducing surface residue, and can help to maintain the uniformity of seed spacing and seeding depth. The newly designed row cleaner generally performed better at forward speed of 6 km/h, based on the distribution of seeds along rows and seeding depth uniformity. Keywords: row cleaner, corn production, no-till planter, wheat residue management, annual double cropping system DOI: 10.3965/j.ijabe.20150805.1846 Citation: Yang L, Zhang R, Gao N, Cui T, Liu Q W, Zhang D X. Performance of no-till corn precision planter equipped with row cleaners. Int J Agric & Biol Eng, 2015; 8(5): 15－25.